2019
DOI: 10.1186/s12910-019-0383-9
|View full text |Cite
|
Sign up to set email alerts
|

A reflection on ethical and methodological challenges of using separate interviews with adolescent-older carer dyads in rural South Africa

Abstract: Background This article discusses our reflections on ethical and methodological challenges when conducting separate interviews with individuals in dyads in the uMkhanyakude district, South Africa. Our work is embedded in an ethnographic study exploring care relationships between adolescents and their older carers in the context of a large-donor funded HIV programme. We use these reflections to discuss some of the challenges and present possible management strategies that may be adopted in conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Examples include, “Daughter's Responsibilities,” “Relationships,” “Norms,” “Knowledge,” and “Disability.” After organizing into these categories, I went through the interviews again, writing memos about emergent themes. Though I have full dyadic interviews, I do not place these in direct comparison in this article, as this could pose threats to confidentiality (Gumede et al, 2019). In analysis, I take mother and daughter reports as their understanding of what happened.…”
Section: Methodsmentioning
confidence: 99%
“…Examples include, “Daughter's Responsibilities,” “Relationships,” “Norms,” “Knowledge,” and “Disability.” After organizing into these categories, I went through the interviews again, writing memos about emergent themes. Though I have full dyadic interviews, I do not place these in direct comparison in this article, as this could pose threats to confidentiality (Gumede et al, 2019). In analysis, I take mother and daughter reports as their understanding of what happened.…”
Section: Methodsmentioning
confidence: 99%
“…A major pre-requisite for men and women to develop greater interest in biomedical information about implants rests on the assumption that current perspectives amongst young people remain unchanged and do not become indoctrinated by changing social roles over time. Using dyad interview techniques provided richness to our analysis around shared decision making but our ability to represent the data using direct quotes was challenged by the well described ethical constraints of exposing participant identity [51]. Importantly our study findings are based on participant recounts rather than observed behaviours and we should be circumspect in interpreting these findings and extrapolating their longitudinal impact.…”
Section: Limitationsmentioning
confidence: 99%
“…Eligible participants needed to (1) be aged between 18 and 39 years; (2) self-identify as lesbian, gay, or bisexual; (3) reside in Taiwan, holding citizenship or permanent residency; and (4) agree to refer a parent to take part in an interview. In light of the challenges in recruiting both LGB individuals who are "hard-to-reach, stigmatized, [and] hidden" (Guest et al, 2006) and consenting dyads (Gumede et al, 2019), purposive sampling was undertaken via multiple recruitment sites. We distributed: (1) recruitment flyers to LGBrelated service agencies such as Tongzhi Hotline Association (in Taipei), Sunshine Queer Centre (in Kaohsiung), and Taichung G-Di (in Taichung); (2) recruitment advertisements on social media (e.g., Facebook) and smartphone communication applications frequented by LGB individuals (e.g., Grindr, Jack'd, Blued).…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…All interviews were audio-recorded, and audio recordings were encrypted and stored on a password-protected computer accessible only to the PI and research assistant who guaranteed to protect participants' personal identity and information throughout the research process, including in any resultant reports or publications. Dyadic interviews may raise particular ethical concerns regarding confidentiality and the relationship between dyads and may possibly undermine the freedom of narration (Bjornholt & Farstad, 2014;Gumede et al, 2019). In response, we conducted interviews with LGB participants and their parents separately and reassured participants that their accounts would not be disclosed to the other party.…”
Section: Ethical Issuesmentioning
confidence: 99%
See 1 more Smart Citation